IMPLEMENTASI PUBLIC RELATIONS DALAM MEMBANGUN CITRA POSITIF UNIVERSITAS ABDURRAB PEKANBARU - Nadyatul Khairina; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Public Relations basically serves to establish relationships with the public, especially in creating, building and maintaining a positive image to boost the company's image. Public relations position in establishing good relations with the community is very important, especially for getting a positive image. This study aims to find out how to use media in building a positive image of Abdurrab University and how the implementation of public relations events in building a positive image of Abdurrab University pekanbaru.This research uses qualitative methods by using Lasswell Communication Model. Subject of this research consisted of 7 informants selected through snowball technique. Data collected through observation, interview and documentation. To test the validity of the data the author uses an extension of participation and triangulation.The results of this study show the public relations of Abdurrab University chose the media as an effort to introduce the Abdurrab University to the public by using online media, print media and broadcast media used by the public relations Of the Abdurrab University in building a positive image. Online media and print media is a medium that is quite effective in disseminating information to the public. While broadcasting media only as a supporting media in socializing Abdurrab University. The second implementation is a socialization event, talkshow, seminars and milad of Abdurrab University. In the implementation of the socialization of Abdurrab University welcomed by the recipient of the information. Talkshows and seminars as a public relations effort in the introduction of Abdurrab University . While the milad of Abdurrab University is quite an impact in spreading the information. Word of mouth communication is quite effective considering the information given directly by others.Key words : Implementation, Public Relations, Abdurrab University